Association of Serum Vitamin D Level with Angiographic Severity of Coronary Artery Disease in Patients of Acute Myocardial Infarction (Cardiovascular Journal, 2023)
Background: Besides conventional risk factors, a novel risk factor hypovitaminosis D may play unique role in the development of coronary artery disease. Evidences suggest that people with low serum vitamin D level  is associated  with risk of acute MI  even after adjusting for the known risk factors. This study was conducted to find out the association between serum vitamin D Level and angiographic severity of coronary artery disease in patients of acute myocardial infarction.Methods: One hundred and four patients of acute myocardial infarction undergoing coronary angiography in DMCH during May 2017 to April 2018 were the study population. The population were divided into 2 groups based on their serum vitamin D level; normal vitamin D   (>30 ng/ml)   and low vitamin D (≤30 ng/ml). Low vitamin D level again divided into 3 groups; insufficient (vitamin D 21 to 30 ng/ml), deficient (Vitamin D 10-20 ng/ml) and severely deficient having vitamin D 36 points was considered as having moderate to severe coronary artery disease. Association between serum vitamin D Level and angiographic severity of CAD was looked for. Results: Seventy seven (74.0%) of study population had vitamin D level ≤ 30 ng/ml, while 27(26.0%) patients had normal level. There was no significant association between common cardiovascular risk factors with vitamin D level. Double or triple-vessel CAD were more frequent in those with vitamin D levels ≤30 ng/ml as compared to those with normal vitamin D levels (>30 ng/ml) (P30 ng/ml) and 46 (92%) patients had low vitamin D (≤30 ng/ml). Mean Gensini score was found 20.8±5.1 in normal vitamin D (>30 ng/ml) and 48.3±13.3 in low vitamin D (≤30 ng/ml) (p36) was found in 54.1% of patients with vitamin D insufficiency (21-30 ng/dl) and 83.3% of patients with vitamin D deficiency (10-20 ng/dl) (p